Nghiên cứu ảnh hưởng của nhiệt độ nung, tỷ lệ mol Ce-Ti-Si đến sự hình thành pha oxit hỗn hợp CeO2-TiO2-SiO2 được tổng hợp bằng phương pháp đốt cháy gel polyvinyl ancol - Nhiệm, Đào Ngọc; Đại, Lưu Minh; Văn, Nguyễn Đức; Chức, Phạm Ngọc; Dũng, Đoàn Trung; Hà Chi, Nguyễn Thị (Vietnam Journal of Chemistry, 2014)
The nanosized CeO2-TiO2-SiO2 mixed oxide powder has been synthesized by the gel combustion method using polyvinyl alcohol (PVA) as polymer basic and mixture of cerium (IV) nitrate, titanium (III) chloride and silane. Effects of preparative parameters on the phase formation of CeO2-TiO2-SiO2 such as Ce-Ti-Si molar ratio, calcination temperature have been investigated and discussed. The results showed that, for the optimized procedure with pH = 1, temperature of gel formation of 80 oC, molar ratio of metal over polyvinyl alcohol of 1/3, molar ratio of Ce-Ti-Si of 1-1-8. The CeO2-TiO2-SiO2 mixed oxides were obtained with the averge grain size of nanopowders up to 97 nm after calcined at 850 oC for 2 hours. Keywords: CeO2-TiO2-SiO2 mixed oxides, cerium(IV) nitrate, titanium (III) chloride, silane, polyvinyl alcohol, combustion method.